2021
DOI: 10.1111/nyas.14581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasound, radial extracorporeal shock waves, and electrical stimulation on rat bone defect healing

Abstract: Fractures associated with osteoporosis are a major public health concern. Current treatments for fractures are limited to surgery or fixation, leading to long‐term bedrest, which is linked to increased mortality. Alternatively, utilization of physical agents has been suggested as a promising therapeutic approach for fractures. Here, we examined the effects of ultrasound, radial extracorporeal shock waves, and electrical stimulation on normal or osteoporotic fracture healing. Femoral bone defects were created i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Since 2009, Li‐ESWT has been extensively used in regenerative medicine 28 . It has been reported that Li‐ESWT promotes angiogenesis, 29 nerve regeneration 30,31 bone formation, 32 and muscular regeneration and so forth 7 . We previously reported that Li‐ESWT activates penile stem cells and promotes regeneration of erectile tissue to improve erectile function 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Since 2009, Li‐ESWT has been extensively used in regenerative medicine 28 . It has been reported that Li‐ESWT promotes angiogenesis, 29 nerve regeneration 30,31 bone formation, 32 and muscular regeneration and so forth 7 . We previously reported that Li‐ESWT activates penile stem cells and promotes regeneration of erectile tissue to improve erectile function 33 .…”
Section: Discussionmentioning
confidence: 99%
“…60,61 Inoue et al applied ultrasonic therapy on ovariectomized rats with bone defects and found robustly increased number and activities of osteoblasts, and reduced positivity for sclerostin+ osteocytes. 62 In the initial stage of fracture, osteoblasts produce enormous inflammatory cytokines, such as COX-2, 54 monocyte chemoattractant protein-1 (MCP-1), 22 and receptor activator of macrophage inflammatory protein-1β (MIP-1β). 22 COX-2 is a key enzyme to the synthesis of PGE2, 63 both of which are capable of inhibiting osteoprotegerin (OPG) and inducing receptor activator of nuclear factor kappa-B ligand (RANKL) expression in osteoblasts for bone formation.…”
Section: Mechanism Of Lipus On Fracture Healingmentioning
confidence: 99%
“…Osteoblasts are essentially important to bone formation 60,61 . Inoue et al applied ultrasonic therapy on ovariectomized rats with bone defects and found robustly increased number and activities of osteoblasts, and reduced positivity for sclerostin+ osteocytes 62 . In the initial stage of fracture, osteoblasts produce enormous inflammatory cytokines, such as COX‐2, 54 monocyte chemoattractant protein‐1 (MCP‐1), 22 and receptor activator of macrophage inflammatory protein‐1β (MIP‐1β) 22 .…”
Section: Mechanism Of Lipus On Fracture Healingmentioning
confidence: 99%
“…BMP-2 plays a major role in osteoblast differentiation by transforming osteoblast precursor cells into mature osteoblasts that form healthy bone [207]. On the other hand, for proteins such as RANKL, which in turn plays a role in osteoclast differentiation [208], a reduced expression was found after exposure ESWs [19,63,80]. Furthermore, cavitation induced by ESWs can cause so-called "microcracks", which is a stimulus for bone remodeling and new bone formation [209].…”
mentioning
confidence: 99%
“…It was demonstrated in bones of horses that fESWs can induce new microcracks, and rESWs can extend the length of existing microcracks [102]. When looking at the effects of ESWT on the activity of different cell types, an increase in activity in tissue-specific cells such as fibroblasts [68,124] and osteoblasts [39,83], but at the same time a reduced activity of osteoclasts [19] was observed. Together with the reduced RANKL expression this could indicate a positive effect of ESWT on bone formation, as well as an improvement of diseases affecting the skeletal system such as osteoporosis.…”
mentioning
confidence: 99%